Systemic inflammation and liver damage in HIV/hepatitis C virus coinfection. Issue 8 (17th May 2016) - Shmagel, KV; Saidakova, EV; Shmagel, NG; Korolevskaya, LB; Chereshnev, VA; Robinson, J; Grivel, J‐C; Douek, DC; Margolis, L; Anthony, DD; Lederman, MM
Abstract : Objectives: Chronic hepatitis C virus (HCV) and HIV viral infections are characterized by systemic inflammation. Yet the relative levels, drivers and correlates of inflammation in these settings are not well defined. Methods: Seventy‐nine HIV‐infected patients who had been receiving antiretroviral therapy (ART) for more than 2 years and who had suppressed plasma HIV levels (< 50 HIV‐1 RNA copies/mL) were included in the study. Two patient groups, HCV‐positive/HIV‐positive and HCV‐negative/HIV‐positive, and a control group comprised of healthy volunteers ( n = 20) were examined. Markers of systemic inflammation [interleukin (IL)‐6, interferon gamma‐induced protein (IP)‐10, soluble tumour necrosis factor receptor‐I (sTNF‐RI) and sTNF‐RII], monocyte/macrophage activation [soluble CD163 (sCD163), soluble CD14 and neopterin], intestinal epithelial barrier loss [intestinal fatty acid binding protein (I‐FABP) and lipopolysaccharide (LPS)] and coagulation (d ‐dimers) were analysed. CD4 naïve T cells and CD4 recent thymic emigrants (RTEs) were enumerated. Results: Plasma levels of IP‐10, neopterin and sCD163 were higher in HCV/HIV coinfection than in HIV monoinfection and were positively correlated with indices of hepatic damage [aspartate aminotransferase (AST), alanine aminotransferase (ALT) and the AST to platelet ratio index (APRI)]. Levels of I‐FABP were comparably increased in HIV monoinfection and HIV/HCV coinfection but LPS concentrations were highest in HCV/HIV coinfection, suggesting impaired hepatic clearance of LPS. Plasma HCV levels were not related to any inflammatory indices except sCD163. In coinfected subjects, a previously recognized relationship of CD4 naïve T‐cell and RTE counts to hepatocellular injury was defined more mechanistically by an inverse relationship to sCD163. Conclusions: Hepatocellular injury in HCV/HIV coinfection is linked to elevated levels of certain inflammatory cytokines and an apparent failure to clear systemically translocated microbial products. A related decrease in CD4 naïve T cells and RTEs also merits further exploration.